Sustained bloodstream release of persistent organic pollutants induced by extensive weight loss after bariatric surgery: Implications for women of childbearing age - Fénichel, Patrick; Coquillard, Patrick; Brucker-Davis, Françoise; Marchand, Philippe; Cano-Sancho, German; Boda, Mireille; Antignac, Jean-Philippe; Iannelli, Antonio; Gugenheim, Jean; Le Bizec, Bruno; Chevalier, Nicolas (Environment international, 2021)
•One year after surgery, serum POPs levels increased up to 35 to 130%.•Increases depended on weight loss, gender and POP’s lipophilicity.•After one year, ∑PCB6 exceeded critical threshold in 25% women of childbearing age versus 3.6% before.•Fetal and infant health risks should be considered for recommendations in obese women. Lipophilic persistent organic pollutants (POPs) are stored in adipose tissues and released in case of weight loss. To analyze the kinetics and characteristics of this release during drastic weight loss after bariatric surgery and compare the results in case of women of childbearing age (WCBA) with critical blood concentration thresholds. 100 morbidly obese patients (73 women including 53 of childbearing age and 27 men) were screened before and 3, 6 and 12 months after bariatric surgery for serum concentrations of 67 congeners or metabolites of banned or not yet banned organohalogenated persistent pollutants, including highly lipophilic polychlorobiphenyls (PCBs), organochlorine pesticides (OCPs), brominated flame retardants (BFRs), and less lipophilic perfluorinated alkylated substances (PFASs). Circulating levels of all chemicals, except PFASs, increased progressively after surgery, reaching after one year an increase between 30 and 139% compared to initial pre-surgical levels; median levels increased for PCB153 from 36.8 to 86.4 ng/g lw (+130%), for dichlorodiphenyldichloroethylene (p,p’-DDE) from 59.8 to 136.1 ng/g lw (+120%), and for hexachlorobenzene (HCB) from 9.8 to 20.3 ng/g lw (+110%). Weight loss averaging 30% of initial body weight at 12 months in both sexes (mean: 40.0 kg for men, 36.1 kg for women), was the main parameter related to the concentration increases (3.1 to 3.6% per kilogram weight loss). They were not dependent on initial BMI, presence of metabolic syndrome or type of surgical procedure but influenced by gender and biochemical properties such as degree of chlorination for PCBs and/or lipophilicity since PFASs did not increase at all. ∑PCB6 in blood after one year exceeded the critical concentration threshold for 24.5% women of childbearing age (13/53) versus 3.6% (2/53) before surgery. Massive weight loss within the first year following bariatric surgery is associated with a sustained increase of circulating lipophilic POPs. Short- and long-term consequences should be considered, mostly for childbearing age obese women, because of potential health risks for the future fetus and breastfeeding infant.